LO61: A national needs assessment on quality improvement and patient safety education in Canadian emergency medicine residency programs. (May 2019) - Trivedi, S.; Hartmann, R.; Hall, J.; Nasser, L.; Levac-Martinho, O.; Porplycia, D.; Kwok, E.; Chartier, L.
Abstract : Introduction : Quality improvement and patient safety (QIPS) are increasingly recognized as integral to the provision and advancement of emergency medicine (EM) care. In 2015, QIPS were added to the Canadian Medical Education Directives for Specialists (CanMEDS) framework. However, the level of QIPS education and support that Canadian EM residents receive is unknown. In order to better plan national QIPS efforts aimed at enabling EM residents to improve their local care settings, we sought to assess the current state of QIPS education and support in Canadian EM residency programs.Methods : This was a descriptive, cross-sectional electronic survey that was disseminated to all current Canadian EM residents from both Royal College (RC) and Family Medicine - EM training streams. Residents were recruited either directly or through their program's administrative assistant. The survey consisted of multiple-choice, Likert and free-text entry questions. Themes included a) familiarity with QIPS; b) local opportunities for QIPS projects and mentorship; and c) desire for further QIPS education and involvement. The survey was open for a five-week period, with formal reminders after the first and third weeks. Descriptive statistics are reported.Results : 189 (35%) of 535 current EM residents completed the survey, representing all 17 medical schools. 77% of respondents were from the RC stream. 54.7% of respondents reported being "somewhat" or "very" familiar with QIPS. 47.2% of respondents reported "not knowing" or "not having readily available" QIPS projects to participate in their local environment, and 51.5% had equivalent responses with respect to QIPS mentorship opportunities. Only 17.5% of respondents reported that QIPS methodologies were already formally taught in their residency program, and 66.9% indicated a desire for increased QIPS teaching. The majority of respondents were "slightly" (35.9%), "moderately" (23.2%) or "very" (11.3%) interested in becoming involved with QIPS training and initiatives.Conclusion : Responding Canadian EM residents are interested in obtaining greater QIPS education as well as project and mentorship opportunities, but many perceive that they do not have adequate access to these at the current time. As the importance of QIPS increases in the EM community, supporting residents with more robust educational infrastructures may be necessary. Future efforts may include the standardizing of QIPS postgraduate curricula and improving access to QIPS opportunities across the country.